The effects of Mergers and Acquisition on the Profitability and Cost Efficiency of Malaysian Banks. - Paul Palasupramaniam, Edward Thangaratnam (2009)
The research conducted in this study is to investigate the impact of mergers and acquisitions on local banks in Malaysia. This is especially important as there are few studies done in this field and the number of banks going through the mergers and acquisition process is increasing. In this study a quantitative method will be used to evaluate the newly formed banks to measure their efficiency and profitability. A survey of available literature on mergers and acquisitions in Malaysia shows that there are some improvements in cost efficiencies of local banks after a merger or acquisition. However, despite the increase in revenue generated from the newly formed banks, profits from such banks were much lower compared to banks with similar merger or acquisitions in Europe or the US. Despite this fact, Bank Negara Malaysia have been encouraging banks to opt for mergers or acquisitions to reduce the number of banks in the Malaysian banking system, and also to create banks that are more financially stable. 9 Malaysian banks, 7 of which were formed though mergers or acquisitions and the other two which remained the same from inception were chosen. Data for this study was collected from standardised annual reports taken from the Bloomberg database. From the data, a logistic regression model was created using SPSS. A logistic regression is created from a Linear Probability Model where, the dependant variable only takes two values, 0 and 1. This model was used to compare the banks’ individual performance in terms of profitability and their ability to improve cost efficiency. From the results of the tests done using the logistic regression it was found that the variables LABORCOST and INTERBANK used to determine cost efficiencies of banks were not very significant. Therefore, banks that chose to go through a merger or acquisition do not have significant improvements in costs. Nevertheless, mergers or acquisitions of banks were found to be more profitable, based on the revenues earned from services and Interbank balances held with other banks.